Dynamic lateral load testing of deep foundation groups - Chakraborty, Sanjoy (ProQuest Dissertations & Theses, 2000)
Bridge foundations are subject to dynamic lateral loads in the form of ship impacts and earthquakes, which usually involve the transfer of large amounts of energy to the foundation in short periods of time. Such loading conditions must be accounted for during design of new bridges or retrofit of existing bridges. There is no simple way to predict how a foundation will react to dynamically applied lateral loads, since the response of the system under such conditions is usually highly nonlinear. In addition, not much data are available from tests that attempt to simulate large amplitude high energy loading conditions on full scale foundation groups, as such testing is extremely expensive. This dissertation describes a series of large amplitude static and dynamic lateral tests conducted on fully instrumented deep foundations groups at two separate geographic locations. The static load tests were carried out using conventional hydraulic systems, while a series of dynamic loads were applied to each foundation using the Statnamic device. The foundations tested were meant to represent the most commonly used structural types, and included groups founded on prestressed concrete piles, large diameter concrete drilled shafts, and hollow steel pipe piles. The thrust of the study was twofold. A primary analysis was conducted on the large volumes of data generated by the testing program. This included the derivation of static and dynamic response parameters like displacements, accelerations, bending moments and axial stresses, shear distribution patterns within groups, and changes in system behavior with increasing levels of load and nonlinearity. Analysis of the test data indicated that Statnamic loading can mobilize significant dynamic soil resistance. The larger Statnamic tests also induced significant nonlinearities in the foundation and soil, which resulted in decreased stiffness and period elongation, permanent set, and sometimes gapping in the soil. Group effects and the distribution of shear loads to individual piles in the group could be predicted with reasonable accuracy under static loading conditions. The dynamic response of the pile cap could be modeled using a simplified equivalent single degree of freedom (SDOF) model. The SDOF model was also used to predict the static load-deflection and total soil resistance functions of the foundations with a good deal of success. (Abstract shortened by UMI.)